2014
DOI: 10.3324/haematol.2013.096859
|View full text |Cite
|
Sign up to set email alerts
|

The importance of calcium in the regulation of megakaryocyte function

Abstract: © F e r r a t a S t o r t i F o u n d a t i o ndepletion and activates Orai1 (also known as calciumrelease-activated calcium-modulator, CRACM), the poreforming subunit of store-operated Ca 2+ channels. 19 The role of the additional STIM1 and Orai1 paralogs, i.e. STIM2 and Orai2-3, is far from being fully understood in naïve cell systems, albeit they may recapitulate SOCE when ectopically expressed. 19 Moreover, several evidences demonstrated that members of the canonical transient receptor potential (TRPC) fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 51 publications
(93 reference statements)
0
49
0
Order By: Relevance
“…Previous work showed that extracellular Ca 2+ entry regulates actin polymerization,23 so we stained cells with phalloidin to visualize actin fibers (Figures 5D and S9). Control megakaryocytes displayed obvious signs of actin reorganization, including peripheral enhancement of staining, focal complex formation, and peripherally extending filaments (Figure 5D.i).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that extracellular Ca 2+ entry regulates actin polymerization,23 so we stained cells with phalloidin to visualize actin fibers (Figures 5D and S9). Control megakaryocytes displayed obvious signs of actin reorganization, including peripheral enhancement of staining, focal complex formation, and peripherally extending filaments (Figure 5D.i).…”
Section: Resultsmentioning
confidence: 99%
“…Refilling these stores occurs through store-operated calcium entry (SOCE; Putney, 1986). This is the major mechanism that triggers Ca 2+ influx in non-excitable cells (Parekh and Putney, 2005; Abdullaev et al, 2008; Sánchez-Hernández et al, 2010; Di Buduo et al, 2014). The key proteins that are involved in this process are Ca 2+ sensors that are located in the ER (stromal interaction molecule 1 [STIM1] and STIM2) and Ca 2+ channel-forming proteins (Orai1–3) that are present in the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Further, increasing evidences have recently identified the contribution of SOCE in thrombopoiesis, the process that ensures the differentiation of megakaryocytes, the platelet precursors, and final platelet production [28]. …”
Section: Introductionmentioning
confidence: 99%